Perancangan Alat Peringatan Dini Banjir dengan Sensor HC SR-O4 Dan NODEMCU Berbasis IOT - Aldin Tegar Wahyudi; Diana Yusuf; Elliya Sestri (Jurnal Teknologi Informasi (JUTECH), 2022)
With current technological advances we can minimize or possibly prevent the effects of flooding by utilizing IoT (Internet of Things). On January 1, 2020 the volume of water in Cisadane overflowed which resulted in Panungnggang Barat Village being submerged by floods reaching 2.5 meters which had reached the roofs of houses, causing residents to flee their homes, look for medicines due to itching, and lose some of their assets. Panungnggang Barat Village currently does not have a tool to warn of flooding if at any time the Cisadane river overflows, therefore this research was made to make a flood early warning tool for residents to be vigilant if at any time the volume of water in the Cisadane river overflows into settlements. By focusing on research, observation, and interviews related to the matter being researched, researchers have observed and analyzed the problems in the Panungnggang Barat Village that there are no flood early warning devices, so residents are only guessing when the flood will come. From the problems that have been described, the researcher aims to create a flood early warning tool so that it can be useful for residents of Panungnggang Barat Village if at any time the water in the Cisadane River overflows, this tool will function as a warning to residents to be prepared for floods.